Evaluating the quality of training programs for pre-service music teachers in chinese higher education institutions - Wencui Huang; Rosy Binti Talin (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
This research utilized an explanatory sequential design within a mixed-methods framework to assess the effectiveness of three pre-service music teacher programs aimed at Grades 1-12 in China. First, a group of four evaluators was asked to holistically assess the overall quality of these programs on a scale ranging from 1 to 10. Second, the evaluators were invited answer four openended questions about the areas for improvement in terms of program goals and objectives, program curricula, instructional methods, and learning assessments, respectively. The generalizability (G-) theory framework was employed to analyze the quantitative data, particularly to examine the variability in ratings and the reliability of the program evaluations. The qualitative data underwent coding, categorization, and organization according to recurring themes. The results indicated that the rating of the quality of these programs by the four program evaluators was extremely consistent and unbelievably reliable. Furthermore, major areas for improvement are identified in program objectives and curricula as well as instructional methods and learning assessments. Implications for pre-service music teacher training program developers in Chinese colleges and universities are discussed.